Simfoni No. 40 Bagian Pertama Wolfgang Amadeus Mozart - F. XAVERIA DIAH K (Institut Seni Indonesia Yogyakarta, 2008)
The First Symfoni No 40 Wolfgang Amadeus Mozart. Symphony is a great composition, whichconventionally consists of four parts. At the end of the eighteenth century it became the main format of orchestralmusic. However, it became prominent at the time of Beethoven. Symphony is a great and ambitious piece of musicsince it is played for 20-45 minutes in length, containing an expansion of tone colors and dynamics of classicalorchestra. It has been known that classical symphony usually consists of four parts inciting broader emotion bythe created tempo and nuance. Mozart’s three last symphonies are Mozart’s masterpieces and Symphony No. 40,for example, contains connotations of romantic signs ignored by his predecessors. Although Symphony No. 40employs minor tones, it is not sad but cheerful, playful, passionful, and dramatic. The fi rst part of the Symphonyuses Allegro Sonata format which consists of three parts, namely exposition, development and recapitulation.